Effectiveness of Learning Breaststroke Swimming with a Visualization Model of Basic Swimming Movement in High Grade Students at SD Negeri 8 Metro Center - Arsy Chandni Naratama; Herman Tarigan; Ardian Cahyadi; Fransiskus Nurseto; Boy Sembaba Tarigan (Jurnal Pendidikan Jasmani (JPJ), 2023)
This study aims to identify the effectiveness of learning breaststroke swimming with a visualization model of basic swimming motion in elementary school students at SD Negeri 8 Metro Pusat. The method used is the experimental method with a population of 20 students. The sample used is total sampling by taking a sample where the entire population is students of SD Negeri 8 Metro Pusat, totaling 20 people. From the results of the data analysis research, it was obtained that t-count = 15 > t-table = 2.262 significant level α 5% for male students and t-count = 13.856 > t-table = 2.262 significant level α 5% for female students, degrees of freedom dk = N-1 = 10-1 = 9, which means that there is a significant difference in the pre-test and post-test data for boys and girls. Because t-count 15 > t-table 2.262 for male students and t-count 13.856 > t-table 2.262 it can be concluded that there is an application of an effective visualization learning model for the basic motion of breaststroke swimming in high grade elementary school students at SD Negeri 8 Metro Pusat (accepted).